Reading digital texts: new literacy practices? - Godoy, Lucía (2023)
This article investigates digital reading practices in secondary school educational spaces. From the framework of the New Literacy Studies, we analyze scenes in Language and Literature classrooms of second year secondary level which were recorded during a fieldwork with an ethnographic perspective. The purpose of the article is to account for the characteristics of literate practices in order to analyze how digital texts are read and how is the inclusion of digital technologies in the reading process. From the analysis of digital reading scenes in the classroom, we propose, first, a categorization to classify the different types of digital texts according to their forms of production, circulation and affordances. Secondly, based on the observations, it is suggested that it is necessary to be cautious about changes in reading practices with digital technologies, since it is not always when digital technologies are incorporated that one can speak of new literate practices and literacies, but only of new supports. For this reason, the innovative character of reading practices will depend on the activities and knowledge expressed in the classroom.